Odpowiedzi

2010-02-15T15:58:10+01:00
2010-02-15T16:06:31+01:00
-[-(-7)-(-4)×(-2):(-¼|)×(-2)-(-55)]×(-3)=
-[7 + 4 * (-2) : (-1/4) * (-2) + 55] * (-3)=
-[7 - 8 : (-1/4) * (-2) + 55] * (-3)=
-[7+32 * (-2) +55] * (-3)=
-[7 - 64 +55] * (-3)=
-(7-9) * (-3)=
-(-2) * (-3)=
2*(-3)=
-6
10 4 10
Najlepsza Odpowiedź!
2010-02-15T16:07:02+01:00
B. -6

bo

-[-(-7)-(-4)×(-2):(-¼|)×(-2)-(-55)]×(-3) =
-[7+4×(-2):(-0,25)×(-2)+55]×(-3) =
-[7+(-8):(-0,25)×(-2)+55]×(-3) =
-[7+32×(-2)+55]×(-3) =
-[7+(-64)+55]×(-3) =
-(-2)×(-3) = 2×(-3) = -6

ps. naj rozwiązanie? ;)
pozdrawiam
29 4 29